Therapeutic resurgence of 6-diazo-5-oxo-l-norleucine (DON) through tissue-targeted prodrugs - Novotná, Kateřina; Tenora, Lukáš; Slusher, Barbara S; Rais, Rana (Advances in pharmacology (San Diego, Calif.), 2024)
The recognition that rapidly proliferating cancer cells rely heavily on glutamine for their survival and growth has renewed interest in the development of glutamine antagonists for cancer therapy. Glutamine plays a pivotal role as a carbon source for synthesizing lipids and metabolites through the TCA cycle, as well as a nitrogen source for synthesis of amino acid and nucleotides. Numerous studies have explored the significance of glutamine metabolism in cancer, providing a robust rationale for targeting this metabolic pathway in cancer treatment. The glutamine antagonist 6-diazo-5-oxo-l-norleucine (DON) has been explored as an anticancer therapeutic for nearly six decades. Initial investigations revealed remarkable efficacy in preclinical studies and promising outcomes in early clinical trials. However, further advancement of DON was hindered due to dose-limiting gastrointestinal (GI) toxicities as the GI system is highly dependent on glutamine for regulating growth and repair. In an effort to repurpose DON and mitigate gastrointestinal (GI) toxicity concerns, prodrug strategies were utilized. These strategies aimed to enhance the delivery of DON to specific target tissues, such as tumors and the central nervous system (CNS), while sparing DON delivery to normal tissues, particularly the GI tract. When administered at low daily doses, optimized for metabolic inhibition, these prodrugs exhibit remarkable effectiveness without inducing significant toxicity to normal tissues. This approach holds promise for overcoming past challenges associated with DON, offering an avenue for its successful utilization in cancer treatment.
Keywords: Animals; Metabolic inhibition; Prodrugs; Neoplasms; nádory; glutamin; Gastrointestinal; lidé; Antineoplastic Agents; protinádorové látky; Diazooxonorleucine; prekurzory léčiv; Glutamine addiction; Glutamine; 6-Diazo-5-oxo-L-norleucine (DON); Glutamine antagonist; Prodrug; zvířata; diazooxonorleucin; Humans